Implementasi Kepemimpinan Kepala Sekolah terhadap Peningkatan Profesionalisme Guru - Maratul Qiftiyah; Rina Rahmi; Septika Laily Anti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This article aims to determine the implementation of the principal's leadership towards improving teacher professionalism. This research uses a qualitative approach with the method of library research. The data collection techniques used are by examining or exploring several journals, books, and documents (in print or electronic form) as well as other data sources that are considered relevant to this article. The findings of this article are based on eight principals of school leadership that can be applied to develop their schools. The principles in question consist of constructive, creative, participatory, cooperative, delegative, integrative, rational, pragmatic, exemplary, and adaptable and flexible. Where the principal is responsible for fostering and forming professional teachers in order to build quality schools. Therefore, Principal leadership and teacher professionalism are two factors that influence each other.